όκως no subordinado en el Corpus Hipocrático - González Martín, Ana María (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2007)
In the Hippocratic Corpus, όκως possesses, besides its common function as hypotactic conjunction, a less common value as independent-sentence introducer, which has traditionally been interpreted as an elliptical construction (v. cavendi, efficiendi ...) Our objective in this paper is not just to define syntactical and semantically this kind of construction in order to establish its value, but also to study the relationship between this marginal use and the most common value of o{kw" as hypotactic conjunction.